Discussion of The Effect of Aggregating Accounting Reports on the Quality of the Lending Decision: An Empirical Investigation - Edmister, Robert O. (Journal of Accounting Research, 1973)
Robert O. Edmister, Discussion of The Effect of Aggregating Accounting Reports on the Quality of the Lending Decision: An Empirical Investigation, Journal of Accounting Research, Vol. 11, Empirical Research in Accounting: Selected Studies 1973 (1973), pp. 139-142